Knowledge, attitude and practice on the Islamic Perspective Slots (IPS) in biomedical science curriculum among biomedical science students of International Islamic University Malaysia - Mohd Shafri, Mohd Affendi; Jamil, Ainaaul Mardhiyah; Shahdan, Intan Azura; Abdul Rahman, Norazlina (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
The Islamic perspective slot (IPS) is a strategy to enhance the agenda of Islamisation of Knowledge in the curriculum of the Department of Biomedical Science (DBMS) at the Kulliyyah of Allied Health Sciences (KAHS), International Islamic University Malaysia (IIUM). Here, the outcome of a 4-year implementation of the IPS is assessed by determining the knowledge, attitude and practices on the IPS in the Biomedical Science curriculum among IIUM Biomedical Science students. A cross-sectional study was performed using convenience sampling on 205 students administered with a self-guided questionnaire. The total score for each knowledge, attitude and practice were computed to find the association using SPSS. The total mean and standard deviation of knowledge, attitude and practice score were found to be 20.18±3.60, 89.47±12.99 and 38.22±6.94 respectively. There was weak positive correlation between knowledge and attitude (r=+0.286; p<0.001), and knowledge and practice (r=+0.246; p<0.001), and fair positive correlation between attitude and practice (r=+0.564; p<0.001). Significant association was also established between year of study and knowledge (p<0.001), attitude (p<0.001) and practice (p<0.001). Additionally, there were significant differences between gender with knowledge (p = 0.009) and attitude (p=0.016). However, there was no significant difference between gender in terms of practice (p=0.059). Educational background did not appear to influence knowledge (p=0.198), attitude (p=0.147) and practice (p = 0.876). The study revealed that overall students’ score on knowledge is moderate, whereas score on attitude is good and score on practice is low. The results revealed that the current practice involving the IPS is yet to achieve satisfactory outcome, improvements must be made and the study to be repeated again after improvements are made.